INTEGRATED BIOLOGICAL TECHNOLOGY TO CONTROL MUNGBEAN PESTS AND DISEASES - Marida Santi Yudha Ika Bayu; Yusmani Prayogo; Gatut Wahyu Anggoro Susanto (Indonesian Journal of Agricultural Science, 2021)
The main constraints to increase mungbean production in Indonesia are pests and diseases. The application of integrated biological agents can improve the efficacy of controlling the mungbean pests and diseases. The study aimed to determine the efficacy of integrated biological agents to suppress mungbean pests and diseases. This field research was conducted from May to July 2018 using a randomized block design with seven treatments and four replicates. The treatments were: T1 = Trichol + NSP, T2 = Trichol + SlNPV, T3 = Trichol + NSP + SlNPV, T4 = Trichol + NSP + SlNPV + BeBas, T5 = Trichol + NSP + SlNPV + BeBas + GE, T6 = chemical pesticides, and T7 = control. The results showed that the highest efficacy occurred in T4 and T5 treatments which saved the yield loss from major pests and diseases attack, and did not differ significantly with chemical pesticides (T6). Treatments T4 was able to reduce the development of soil borne diseases by 3% and suppress Spodoptera litura attack by 9.8% as compared to chemical treatment. T4 was also more efficient than T5 because it uses less biological agents. The advantage of biological agents is compatible if they were used together with predators such as Oxyopes sp., Paederus sp. and Coccinella sp; and also Telenomus sp. and Trichogramma sp. parasitoids. On the other hand, the chemical pesticides (T6) killed all existing natural enemies. Therefore, T4 could be recommended for controlling mungbean pests and diseases.